Pallenberg - Singer. - Kosch, Wilhelm (De Gruyter, 1992)
The Deutsches Theater-Lexikon [Dictionary of German Theatre] provides a host of information on every aspect of the stage. It comprises meticulously researched contributions on actors, singers, directors, playwrights and theatre managers etc. In addition, it defines significant key words and organizational structures, and portraits outstanding playhouses and venues. The dictionary lists date and place of first nights of plays, operas and operettas; biographical dates of artists; as well as chronological listings of the performers' engagements. Each entry contains a bibliography of relevant seco.